A Systematic Study on the Stability of Porous Coordination Polymers against Ammonia. Issue 47 (14th October 2014) - Kajiwara, Takashi; Higuchi, Masakazu; Watanabe, Daisuke; Higashimura, Hideyuki; Yamada, Teppei; Kitagawa, Hiroshi
Abstract To establish a strategy for designing porous coordination polymers (PCPs) for ammonia capture, the first systematic study on the stability of PCPs against ammonia was conducted. Various types of PCPs were investigated by comparing their powder XRD patterns before and after treatment with ammonia. Among the PCPs tested, ZIF‐8, MIL‐53(Al), Al‐BTB, MOF‐76(M) (M=Y or Yb), MIL‐101(Cr), and MOF‐74(Mg) were stable up to 350 °C under an ammonia atmosphere at ambient pressure. The origin of the stability of PCPs is discussed from the viewpoint of their components, metal cations, and organic linkers. Furthermore, adsorption isotherm measurements show that the adsorptive behavior of PCPs is independent of their stability.